Mirroring To The Greek’s Tourism after Economy Crisis: The Effect of Tourism Sector to Bangka Belitung GDRP - Royhan Faradis; Uswatun Nurul Afifah (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2018)
High dependency on tin mining is an economic problem in Bangka Belitung Islands province. The peak came after the issuance of tin mining restriction law almost a decade ago, hence Bangka Belitung is currently experiencing a slowdown in the rate of economic growth on an ongoing basis. One way out of this economic problem is to rely on tourism, since the demographically and geographically Bangka Belitung is a world tourist paradise. However, bad tourism management will actually increase development losses. Therefore, this paper will discuss the influence of Bangka Belitung tourism on its economy if tourism were a leading sector as applied in Greece in recent years. In addition, the characteristics of Greece, Santorini in this case, is not much different from Bangka Belitung Islands. In getting the answer from this problem, two methods of analysis are done, namely the Strength, Weakness, Opportunity and Threat (SWOT) table and the formation of simple regression model related to tourism and economy of Bangka Belitung. The results obtained shows that Bangka Belitung's economy will grow positively due to its tourism influence, and with similar characteristics of Bangka Belitung with Santorini then the “4S tourism policy” (sun, sea, sand and seafood) can be applied in Bangka Belitung.